2020
DOI: 10.3390/cancers12040850
|View full text |Cite
|
Sign up to set email alerts
|

L-Glucose: Another Path to Cancer Cells

Abstract: Cancerous tumors comprise cells showing metabolic heterogeneity. Among numerous efforts to understand this property, little attention has been paid to the possibility that cancer cells take up and utilize otherwise unusable substrates as fuel. Here we discuss this issue by focusing on l-glucose, the mirror image isomer of naturally occurring d-glucose; l-glucose is an unmetabolizable sugar except in some bacteria. By combining relatively small fluorophores with l-glucose, we generated fluorescence-emitting l-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 196 publications
2
14
0
Order By: Relevance
“…Pharmacological experiments further revealed that both of the inhibitors against GLUTs and against SGLTs failed to suppress the 2-NBDLG uptake into MIN6 cells [18]. Eventually, we found that the uptake of 2-NBDLG was abolished by phloretin [18], an aglycone of natural polyphenol phlorizin and a broadspectrum inhibitor against membrane transport including GLUTs/water channels [19,20], implying that 2-NBDLG enters the tumor cells through non-GLUT/non-SGLT pathways [4]. Since then, we had been unable to find out other tumor cell lines showing such specific uptake of 2-NBDLG.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Pharmacological experiments further revealed that both of the inhibitors against GLUTs and against SGLTs failed to suppress the 2-NBDLG uptake into MIN6 cells [18]. Eventually, we found that the uptake of 2-NBDLG was abolished by phloretin [18], an aglycone of natural polyphenol phlorizin and a broadspectrum inhibitor against membrane transport including GLUTs/water channels [19,20], implying that 2-NBDLG enters the tumor cells through non-GLUT/non-SGLT pathways [4]. Since then, we had been unable to find out other tumor cell lines showing such specific uptake of 2-NBDLG.…”
Section: Introductionmentioning
confidence: 74%
“…Persistence of the 2-NBDLG uptake in the presence of both cytochalasin B and phlorizin suggested an involvement of a non-GLUT, non-SGLT-mediated mechanism in the uptake of 2-NBDLG in U2OS cells. It is widely accepted that glucose transporters, at least those known to date, all operate by binding of d-glucose to their glucose binding site [4]. Alternatively saying, the uptake of fluorescently labeled glucose analogues could well be competitively inhibited by d-glucose, if it is mediated by glucose transporters.…”
Section: A Possible Involvement Of a Non-stereoselective Non-glut/nomentioning
confidence: 99%
See 3 more Smart Citations